The Processing Technology of Feather Meal and Its Use as a Protein Source in Ruminant Ration - Puastuti, Wisri (Indonesian Animal Sciences Society, 2007)
Feather meal protein contains high level of keratin, which consists of 14% disulphide cystine, therefore feather meal protein is difficult to be digested by proteolytic enzymes. Feather meal must be processed before being used in the ration, because the digestibility of unprocessed feather meal is very low (5.8%). There are four processing methods of feather meal, i.e. physical, chemical, enzymatic and microbiological. The aim of these processings is to alleviate or break down the bonds in the keratin such as disulphide, ionic, ester and hydrogen bonds. Processed feather meal is known as hydrolyzed feather meal (HFM). Although the processing methods of feather meal produce different quality of HFM, the utilization of HFM in ruminant ration results in a better response than conventional protein resources. HFM has higher level of crude protein content (74 â 92%), rumen undegradable protein (70%) and post rumiral digestibility (57 â 78%) than soybean meal has. The utilization of HFM in ration up to 8% of dry matter can substitute soybean meal and the use of 2 â 3% HFM improved milk production in dairy cow and daily gain in sheep and cattle. Â Key words: Hydrolyzed feather meal, protein, ruminant, processing technology